Epidemiology, Mechanisms, and Diagnosis of Drug-Induced Anaphylaxis - Montañez, Maria Isabel; Mayorga, Cristobalina; Bogas, Gador; Barrionuevo, Esther; Fernandez-Santamaria, Ruben; Martin-Serrano, Angela; Laguna, Jose Julio; Torres, Maria José; Fernandez, Tahia Diana; Doña, Inmaculada (Frontiers in Immunology, 2017)
Anaphylaxis is an acute, life-threatening, multisystem syndrome resulting from the sudden release of mediators by mast cells and basophils. Although anaphylaxis is often under-communicated and thus under-estimated, its incidence appears to have risen over recent decades. Drugs are among the most common triggers in adults, being analgesics and antibiotics the most common causal agents. Anaphylaxis can be caused by immunologic or non-immunologic mechanisms. Immunologic anaphylaxis can be mediated by IgE-dependent or independent pathways. The fomer involves activation of Th2 cells and the cross-linking of two or more specific IgE (sIgE) antibodies on the surface of mast cells or basophils. The IgE-independent mechanism can be mediated by IgG, involving the release of platelet activation factor (PAF), and/or complement activation. Non-immunological anaphylaxis can occur through the direct stimulation of mast cell degranulation by some drugs, inducing histamine release and leading to anaphylactic symptoms. Work-up of a suspected drug-induced anaphylaxis should include clinical history, however this can be unreliable, and skin tests should also be used if available and validated. Drug provocation testing is not recommended due to the risk of inducing a harmful reaction. In vitro testing can help to confirm anaphylaxis by analyzing the release of mediators such as tryptase or histamine by mast cells. When immunologic mechanisms are suspected, serum-sIgE quantification or the use of the basophil activation test can help confirm the culprit drug. In this review we will discuss multiple aspects of drug-induced anaphylaxis, including epidemiology, mechanisms and diagnosis.